Biomass as a Source of Household Energy and Indoor Air Pollution in Nepal - Sunil Prasad Lohani (Iranica Journal of Energy and Environment, 2011)
This paper reviews the status of biomass as a source of household energy and indoor air pollution in Nepal. The current statistics show that about 89% of total energy is consumed in residential sector is largely for cooking and heating purpose. The major sources of residential energy are fuel wood (86.5%), animal dung (6.5%) and agricultural residue (3.7%), which clearly indicates a huge demand for biomass as household energy in the country. Several studies have shown that particulate matter (PM10) concentration on cooking place was about 8000 μg/m³ against the national standard of 120 μg/m³ in 24 hours average time. Similarly, the total suspended particle (TSP) was about 8,800 μg/m³ against national standard of 230 μg/m³, 21 ppm of carbon monoxide (CO) against national standard of 9 ppm in 8 hour average was found where biomass was used as fuel. Moreover, these studies have also shown that mortality and morbidity rates among children and women are extremely high due to acute respiratory infection (ARI) and chronic obstructive pulmonary disease (COPD). This clearly indicates that the major cause behind it is indoor air pollution.